(untitled) (Boston, 2009)
Fundamentals of Human Resource Management, by Noe, Hollenbeck, Gerhart and Wright is specifically written to provide a complete introduction to human resource management for the general business manager. This book is the most engaging, focused and applied HRM text on the market.
Keywords: Personnel management